Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.virol.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal tissue pharmacokinetics of the integrase inhibitor raltegravir in a humanized mouse model: Implications for HIV pre-exposure prophylaxis

Abstract: Orally administered anti-retroviral drugs show considerable promise for HIV/AIDS pre-exposure prophylaxis (PrEP). For the success of these strategies, pharmacokinetic (PK) data defining the optimal concentration of the drug needed for protection in relevant mucosal exposure sites is essential. Here we employed a humanized mouse model to derive comprehensive PK data on the HIV integrase inhibitor raltegravir (RAL), a leading PrEP drug candidate. Under steady state conditions following oral dosing, plasma and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Similar trends were seen when studies on mucosal tissue pharmacokinetics of RAL in humanized mice were carried out as in human studies; RAL exhibited higher drug exposure in vaginal and rectal tissues relative to plasma and higher exposure in intestinal mucosa than in plasma [ 51 ].…”
Section: Mouse Studiessupporting
confidence: 52%
“…Similar trends were seen when studies on mucosal tissue pharmacokinetics of RAL in humanized mice were carried out as in human studies; RAL exhibited higher drug exposure in vaginal and rectal tissues relative to plasma and higher exposure in intestinal mucosa than in plasma [ 51 ].…”
Section: Mouse Studiessupporting
confidence: 52%
“…Other recent humanized mice studies have focused on another class of antiretroviral drug. For example, Veselinovic et al (68) used RAG-hu (BALB/c- Rag1 −/− γ c −/− and BALB/c- Reg2 −/− γ c −/− ) mice to test the pharmacokinetic properties of the HIV integrase strand transfer inhibitor raltegravir; the results indicated that raltegravir concentrations were two logs higher in intestinal mucosa and one log higher in vaginal and rectal tissues than in plasma (similar to the trends observed in human subjects). This finding indicates that humanized mice are suitable for preliminary pharmacokinetic preexposure prophylaxis studies, and that raltegravir appears to be a good candidate for HIV preexposure prophylaxis (68).…”
Section: Recent Hiv Studies In Humanized Micementioning
confidence: 99%
“…These studies have demonstrated effective inhibition of HIV-1 replication, reduction of HIV-1 viral load, and protection from multiple high-dose HIV-1 challenges ( 87 , 88 , 89 , 90 ). Other studies using the NSG-BLT model provided valuable insights into HIV-1 treatment, viral evolution, prevention strategies, dose testing, tissue concentration, and pharmacokinetic data ( 74 , 91 95 ). NSG-BLT Hu-mice have also been used to investigate potential treatment methods including anti–human IFN receptor 2 (IFNR2) ( 96 ) and anti-IFN-α/β receptor (IFNAR) antibodies ( 78 ) in conjunction with ARTs to successfully diminish viral reservoir size in lymphoid tissue and delay viral rebound ( 78 , 96 ).…”
Section: Hsc Engraftment Models (Current Generation): Nog Nsg Nrg mentioning
confidence: 99%
“…Different studies reported complete or partial protection against a single dose intrarectal challenge with HIV-1 ( 91 , 94 ). Using the DKO model, tissue distribution of the interventions has also been assessed ( 73 , 74 ). In studies focused on the vaginal route of transmission, many studies examined the efficacy of topical microbicides in DKO and BLT models ( 75 , 92 , 108 116 ).…”
Section: Understanding Mucosal Transmission Of Hiv-1 and The Effect Omentioning
confidence: 99%